2011
DOI: 10.1128/cvi.00064-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunogenicities of Full-Length Plasmodium falciparum Merozoite Surface Protein 3 and a 24-Kilodalton N-Terminal Fragment

Abstract: Recombinant Plasmodium falciparum merozoite surface protein 3 (PfMSP3F) and a 24-kDa fragment from its N terminus (MSP3N) that includes the essential conserved domain, which elicits the maximum antibody (Ab)-dependent cellular inhibition (ADCI), were expressed as soluble proteins in Escherichia coli. Both proteins were found to be stable in both soluble and lyophilized forms. Immunization with MSP3F and MSP3N formulated separately with two human-compatible adjuvants, aluminum hydroxide (Alhydrogel) and Montani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
2
11
0
Order By: Relevance
“…While preparing recombinant MSP3F and MSP3N for immunological characterization studies, we observed that these proteins formed oligomers of high molecular masses (20). The presence of large molecular mass species of MSP3 has been described previously and attributed to the presence of a leucine zipper-like sequence in the C terminus of the protein (7).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…While preparing recombinant MSP3F and MSP3N for immunological characterization studies, we observed that these proteins formed oligomers of high molecular masses (20). The presence of large molecular mass species of MSP3 has been described previously and attributed to the presence of a leucine zipper-like sequence in the C terminus of the protein (7).…”
Section: Discussionmentioning
confidence: 86%
“…These plasmids were transformed in BL21 (DE3) and expressed as soluble proteins. These recombinant proteins were purified under similar conditions as described previously (20). The purified proteins were dialyzed in 20 mM Tris, 150 mM NaCl, pH 8.0, and stored at Ϫ80°C for further experiments.…”
Section: Expression and Purification Of Msp3 Recombinant Proteins-mentioning
confidence: 99%
See 2 more Smart Citations
“…Domain architecture for the P. falciparum msp3 family has been explored previously (Gondeau et al, 2009; Imam et al, 2011). Although one P. falciparum MSP3 protein (PfMSP3.1) shares a region of heptad repeats resulting in predicted coiled-coil tertiary motifs with P. vivax MSP3, the other PfMSP3 proteins lacked the coiled-coil motifs (Jiang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%